Evaluation of the Project P.A.T.H.S. Based on Students’ Weekly Diaries: Findings from Eight Datasets - Daniel T. L. Shek; Rachel C. F. Sun (The Scientific World Journal)
This paper aims to investigate the effectiveness of the Tier 1 Program of the Project P.A.T.H.S. (positive adolescent training through holistic social programmes) based on eight datasets collected between 2005 and 2009. A total of 1,138 students who participated in the program were randomly invited (from the whole grade or in some classes) to write a piece of journal in the form of a weekly diary in order to reveal their perceptions and feelings regarding the program and the perceived benefits of the program. Based on an integration of findings from different databases, results showed that the respondents generally (1) had positive views on the program, (2) had positive views on the instructors, and (3) perceived that they had acquired competencies at the societal, school, familial, interpersonal, and personal levels after joining the program. Acknowledging the limitations of diaries, the present qualitative findings provide support for the effectiveness of the Tier 1 Program of the Project P.A.T.H.S. in Hong Kong.